Simulation Design of Thermal Neutron Collimators for Neutron Capture Studies at The Dalat Research Reactor - Trịnh, Thị Tú Anh (2022)
Background and Objective: The neutron beams at the Dalat nuclear research reactor have been utilized for experimental researchesbased on the neutron capture reaction (n,() and prompt gamma neutron activation analysis. In recent years, a national project has beencarried out for extending and improving the physical characteristics of the beam facilities. The objective of this study is to improve thethermal and epithermal neutron fluxes at the horizontal beamlines of the Dalat reactor. Materials and Methods: The new design ofcollimators and neutron filter selections has been made with optimal parameters for alternative applications. For validation of thesimulation models, the values of neutron flux and gamma dose rate were measured and compared with the simulated values. Results:The simulation of the new collimator system shows that for a crystal filter composition of 60 cm Si and 6 cm Bi, the thermal neutron fluxat the beam port is 4.0×107 n/cm2/s. The selection of crystal filters of 20 cm Si and 3 cm Bi is proposed with higher thermal neutron fluxesof 1.74×108 n/cm2/s, that the thermal neutron component will be improved with a factor of 7.67. Conclusion: A newly designed modelof the conical collimator with a filter combination of 20 cm silicon and 3 cm bismuth, in crystal formations, is proposed for theexperimental study of the in-phantom boron neutron capture measurements